Correlation of Reaction Time on Athletics Triple Jump in High School Students - Yunita Mandasari; Yohanes Joli Krisman Gulo; Zulfitra Asywali Harahap (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. This research aims to determine the influence of reaction time on triple jump athletics in high school students in Medan City. Materials and methods. This type of research is a qualitative associative approach with path analysis. The sample comprised of 30 extracurricular athletic male students taken using total sampling techniques. The instruments used are a triple jump test and a whole body reaction test. The data was analyzed using product moment analysis, then continued with path analysis via a structural model at = 0.05. Results. The results showed reaction time contributed to triple jump ability (r>0.05). The results of reaction time with triple jump ability showed that there was a contribution (r=0.847 and r2=0.719=62.41%) Conclusions. Triple jump athletics is greatly influenced by reaction time and we recommend that in training students the role of reaction time is the influencing factor of physical condition.